Flexible Silicon Dimer Nanocavity with Electric and Magnetic Enhancement - Chengda Pan; Yajie Bian; Yuchan Zhang; Shiyu Zhang; Xiaolei Zhang; Botao Wu; Qingyuan Jin; E Wu (Photonics, 2022)
High-index dielectrics have recently been regarded as promising building blocks in nanophotonics owing to optical electric and magnetic Mie resonances. In particular, silicon is gaining great interest as the backbone of modern technology. Here, silicon dimer nanocavities with different sizes of silicon nanospheres were constructed using a probe nanomanipulation method and interacted with a few-layered R6G membrane to investigate the enhancement of electric and magnetic mode coupling. The evidence of the enhancement of fluorescence and slightly prolonged lifetime of R6G indicated the existence of nanocavities. In addition, the simulated electric and magnetic field distributions and decomposed mode of nanocavity were used to analyze the contribution of electric and magnetic modes to the R6G enhanced fluorescence. Such silicon dimer is a flexible nanocavity with electric and magnetic mode enhancement and has promising applications in sensing and all-dielectric metamaterials or nanophotonic devices.